Landing a scow with passengers on the beach at Nome, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Landing a scow with passengers Nome" Original photograph by Eric A. Hegg 1204; copied by Webster and Stevens 93.A.